Volume 1: Symposia, Parts a and B 2005
DOI: 10.1115/fedsm2005-77175
|View full text |Cite
|
Sign up to set email alerts
|

Vortex Dynamics and Mechanisms for Viscous Losses in the Tip-Clearance Flow

Abstract: The tip-clearance flow in axial turbomachines is studied using large-eddy simulation with particular emphasis on understanding the underlying mechanisms for viscous losses in the end-wall region and the unsteady characteristics of the tip-leakage vortical structures. Systematic and detailed analysis of the mean flow field and turbulence statistics has been made in a linear cascade with a moving end-wall. The tip-leakage jet and tip-leakage vortex are found to produce significant mean velocity gradients, leadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In the downstream locations from the trailing edge, the endwall vortical structures become highly complicated due to the interaction of the tip-leakage vortex, tip-separation vortices, and blade wake. In parallel with the present study, You et al (2005) performed a detailed analysis of the vortex-shedding frequency in the blade wake and the space-time correlations of the velocity fluctuations in the endwall tip-leakage flow, and suggested that the tip-leakage vortex is subject to a pitchwise low-frequency wandering motion. Similar observations have been reported by other experimental and numerical studies in tip-clearance configurations (Zierke & Straka 1996;Wang & Devenport 2004).…”
Section: Resultsmentioning
confidence: 64%
“…In the downstream locations from the trailing edge, the endwall vortical structures become highly complicated due to the interaction of the tip-leakage vortex, tip-separation vortices, and blade wake. In parallel with the present study, You et al (2005) performed a detailed analysis of the vortex-shedding frequency in the blade wake and the space-time correlations of the velocity fluctuations in the endwall tip-leakage flow, and suggested that the tip-leakage vortex is subject to a pitchwise low-frequency wandering motion. Similar observations have been reported by other experimental and numerical studies in tip-clearance configurations (Zierke & Straka 1996;Wang & Devenport 2004).…”
Section: Resultsmentioning
confidence: 64%
“…Analytical studies by Vo [9], Vo et al [13,14], and Jothiprasad et al [15] and cascade studies conducted by Bae et al [16] and Donghyun et al [17] suggest that the optimum location of the actuators is over or slightly downstream of the rotor leading edge to impact the formation of the clearance vortex. As this technology was new for a high-speed compressor, the actuators were not placed directly over the blade tip.…”
Section: Test Setup and Instrumentationmentioning
confidence: 96%
“…Donghyun et al [17] at Stanford University used large-eddy simulation to analyze the energy spectra and space-time correlations of the velocity fluctuations that suggested that the tip leakage vortex is subject to a pitchwise low frequency wandering motion. Measurements by Bae et al [16] in a linear compressor cascade at MIT showed that there exists a peak in the frequency content that is a periodic unsteadiness, which corresponds to the most effective frequency for blockage reduction using a normal synthetic jet.…”
Section: Tip Vortex Dynamics-strouhal Numbermentioning
confidence: 99%
“…At the same region, the most intensive pressure fluctuations These complicated vortexes have a remarkable influence on the flow pattern. Studies on the mechanisms of viscous losses [39][40][41] show that the TLV and leakage flow can lead to violent turbulence intensity, which increases the viscous losses near the tip clearance. Using the results from numerical simulation, You et al proposed strategies to improve the engineering design, such as optimizing the direction of leakage flow by changing the tip shape.…”
Section: Vortex Types and Corresponding Characteristicsmentioning
confidence: 99%